Indirectness Features in Argumentative Essays of Costa Rican EFL University Students - Vargas Vásquez, José Miguel; Zúñiga Coudin, Randolph (Revista de Lenguas Modernas, 2018)
This study aimed to determine the frequency of occurrence of a set of indirectness features in argumentative essays. A taxonomy of indirectness features developed by Hinkel (1997) was employed to classify the features under scrutiny into rhetorical, lexical/referential, and syntactic. The study followed a statistical descriptive design to describe a sample of 30 essays. The essays were written by a group of English as a Foreign Language students in a composition course at the western branch of the University of Costa Rica. The frequency of occurrence of indirectness features was calculated per 100 words with an average number of words in the essays of 798. Additionally, the percentage of each feature compared to total indirectness in the essays and the standard deviations of the frequencies were calculated for the analysis. The results revealed that the four indirectness features representing potential recurrent patterns were subordination, vague determiners, delayed claims, and unneces- sary adjectivals. Due to the rhetorical or lexical nature of the features, the researchers recommend that instructors pay increased attention to vocabulary acquisition and to the organization of ideas when raising awareness of differences in communication style. El objetivo del estudio consistió en determinar la frecuencia con que ocurre un conjunto de características de expresión indirecta en ensayos argumentativos. Se empleó una taxonomía de características de expresión indirecta desarrollada por Hinkel (1997) para clasi car las características estudiadas como retóricas, léxicas/referenciales y sintácticas. El estudio siguió un diseño estadístico descriptivo de una muestra de 30 ensayos escritos por un grupo de estudiantes de Inglés como Lengua Extranjera en un curso de composición en la Sede de Occidente de la Universidad de Costa Rica. La frecuencia de las características de expresión indirecta se calculó por cada 100 palabras, con un promedio de 798 por ensayo. Además, para el análisis se calculó el porcentaje de cada característica con respecto al total de expresión indirecta en los ensayos, así como la desviación estándar de las frecuencias. Los resultados revelaron que las cuatro características de expresión indirecta que representan patrones recurrentes potenciales son: la subordinación, los determinantes ambiguos, las a rmaciones con sujetos en posición débil y las cláusulas adjetivales innecesarias. Debido a la naturaleza retórica o léxica de dichas características, los investigadores recomiendan que los docentes presten mayor atención a la adquisición de vocabulario y a la organización de ideas al crear conciencia de las diferencias en estilos de comunicación.